2019
DOI: 10.1002/pd.5474
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive assessment of fetal central nervous system insult: Potential application to prenatal diagnosis

Abstract: Objective: We have developed novel methods for isolating fetal central nervous system (CNS)-derived extracellular vesicles (FCEs) from maternal plasma as a noninvasive platform for testing aspects of fetal neurodevelopment in early pregnancy.We investigate the hypothesis that levels of defined sets of functional proteins in FCEs can be used to detect abnormalities in fetal neuronal and glial proliferation, differentiation, and survival.Method: Maternal plasma was obtained between 10 and 19 weeks from women wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 31 publications
0
51
0
Order By: Relevance
“…Exosomes can be used as both therapeutic means and ideal biological indicators in central nervous system diseases, and of course, this ability can apply to other diseases as well. The non-invasive nature of exosome analysis means that it can be safely used for prenatal evaluation of fetal central nervous system injury (Goetzl et al, 2019), and diagnostic testing of elderly patients (Cicognola et al, 2019).…”
Section: Conclusion and Overviewmentioning
confidence: 99%
“…Exosomes can be used as both therapeutic means and ideal biological indicators in central nervous system diseases, and of course, this ability can apply to other diseases as well. The non-invasive nature of exosome analysis means that it can be safely used for prenatal evaluation of fetal central nervous system injury (Goetzl et al, 2019), and diagnostic testing of elderly patients (Cicognola et al, 2019).…”
Section: Conclusion and Overviewmentioning
confidence: 99%
“…In addition to the above established and putative roles of EVs within the brain, accumulating evidence suggests that the number and composition of EVs can reflect both healthy and pathological states within the CNS (Fiandaca et al, 2015;Yan et al, 2017;Goetzl et al, 2019;Ohmichi et al, 2019). Although investigations are yet in their infancy, evidence suggests that EVs are found throughout the developing CNS (Morton and Feliciano, 2016) and are likely responsible, at least in part, for normal and pathophysiological brain development in the embryonic and early fetal periods.…”
Section: Biomarker Potential Of Cns-derived Evsmentioning
confidence: 99%
“…A recently revealed key characteristic of small EVs derived from the fetal CNS is that they are able to cross the fetal BBB and the placental barrier into the maternal circulation making them an attractive source of biomarkers (Sheller-Miller et al, 2016;Goetzl et al, 2019). Adsorptive-mediated transcytosis, translocation and passage from the CSF via arachnoid granulations are all proposed mechanisms of small EV transfer from the CNS into the periphery (Thompson et al, 2016;Matsumoto et al, 2017).…”
Section: Biomarker Potential Of Cns-derived Evsmentioning
confidence: 99%
“…They found that reduced expression of EV-transmitting miR-300 and miR-299-5p in amniotic fluid of congenital hydronephrosis could predict renal fibrosis. Interestingly, studies by Goetzl et al showed that EVs derived from fetal central nervous system could be purified from maternal plasma, which was related to the abnormal proliferation and differentiation of neural stem cells [ 100 ]. Therefore, EVs may be a potential way for early prenatal diagnosis of fetal neurological diseases.…”
Section: Evs and Pregnant Disordersmentioning
confidence: 99%